2020
DOI: 10.1186/s12883-020-1607-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of repetitive transcranial magnetic stimulation on the ascending reticular activating system in a patient with disorder of consciousness: a case report

Abstract: Background: We report on a stroke patient with disorder of consciousness (DOC) who underwent repetitive transcranial magnetic stimulation (rTMS) and showed recovery of an injured upper ascending reticular activating system (ARAS) injury, which was demonstrated by using serial diffusion tensor tractography (DTT). Case presentation: A 45-year-old male patient was diagnosed as subarachnoid and intracerebral hemorrhages in the left fronto-parieto-temporal lobes. At 5 months after onset, the patient exhibited a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…Therefore, we believe that the increased neural connectivity to both prefrontal cortices and cingulums in the upper ARAS concurrent with the change in the lower ARAS was responsible for the improvement of consciousness in this patient. In addition, our results appeared to correspond with the results of previous studies reporting increased connectivity to the anterior cingulum and prefrontal cortex, which are important areas of awareness in the brain [3][4][5][6][7][8][9]16].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, we believe that the increased neural connectivity to both prefrontal cortices and cingulums in the upper ARAS concurrent with the change in the lower ARAS was responsible for the improvement of consciousness in this patient. In addition, our results appeared to correspond with the results of previous studies reporting increased connectivity to the anterior cingulum and prefrontal cortex, which are important areas of awareness in the brain [3][4][5][6][7][8][9]16].…”
Section: Discussionsupporting
confidence: 90%
“…In the field of neuroscience, clarification of the neural structures of the ARAS involved in the recovery of consciousness has been an important topic with regard to neurorehabilitation in patients with disorders of consciousness. Diffusion tensor tractography (DTT), which is reconstructed from diffusion tensor imaging (DTI), has enabled the three-dimensional reconstruction of the ARAS, and several DTT studies have reported on changes in the ARAS in patients who showed recovery of impaired consciousness following Recovery of the ascending reticular activating system and consciousness following comprehensive management in a patient with traumatic brain injury rehabilitation [3][4][5][6][7][8][9]. In contrast, only one study reported the positive effect of cranioplasty on impaired consciousness without evidence of change in the ARAS [10].…”
Section: Introductionmentioning
confidence: 99%
“…From the 10 included studies, 8 discussed the safety of the TMS interventions utilized and explicitly reported that no patients experienced adverse effects (24,31,32,(34)(35)(36)(37)(38). The other two studies did not report any adverse effects, although no formal statement concerning safety of TMS was included in either (30,33). Ethical concerns limit the potential for conducting research in this patient population (17).…”
Section: Proposing a Tms Protocol For Doc Patientsmentioning
confidence: 99%
“…In addition, a case report showed that the volume of the neural tract of a patient with DOCs was both temporally and spatially related to the rTMS over the right DLPFC. [ 46 ] Moreover, the left DLPFC has also been used as a therapeutic target, whereby screening was performed to select 16 patients with DOCs with a disease duration of more than 3 months, and in a stable condition, who, then, received 10 Hz rTMS therapy for 20 consecutive days. Among five MCS patients and 11 UWS patients, four patients showed improved consciousness and gained a certain level of communicational ability, [ 47 ] whereas the short disease duration increased the possibility of spontaneous recovery; however, this uncontrolled study provided limited confidence to its evidence.…”
Section: Resultsmentioning
confidence: 99%